Occurrence of surgical affections in zoo herbivores: a retrospective study (Research in Agriculture Livestock and Fisheries, 2018)
Correction: On 21st September 2018, the author 'Pravin Kumar Mishra' was changed to 'Pravin Mishra' - Editorial Board. The study has been directed to find out the occurrence of surgical affections in herbivorous zoo animals in National Zoological Garden, Dhaka, Bangladesh predicated on record books from 2012 to 2016. A total of 330 surgically affected animals were recorded. The overall occurrence of surgical affections was higher in Bovidae (34.85%) followed by Cervidae (25.45%), Equidae (13.94%), Cercopithecidae (10.61%), Giraffidae (4.85%), Elephantidae (4.55%) Hippopotamidae (4%), Rhinocerotidae (1.52%) and Macropodidae (0.61%). In this study, it is found a higher occurrence of surgically affected are male than female animals. The overall occurrence in male was 56.36% and those in female, it was 43.64%. In terms of different affections, the highest occurrence was wound (13.03% male, 16.67% female) and followed by lameness (14.55% in male, 11.82% in female), skin lesions (9.39% in male, 6.67% in female), myiasis (5.76% in male, 3.33% in female), Horn fracture 3.33% (Only in male), arthritis (2.42% male, 1.52% female), hoof injury (1.82% male, 1% female), abscess (1.52% male, 1.21% female), sore (0.61% male, 2.12% female), Fracture (1.21% male, 0.3% female), Paralysis (0.61% male, 0.3% female) and Corneal opacity (0.61% male, 0.3% female). This report may help to develop control strategies against major surgical affections reported in this study.Res. Agric., Livest. Fish.5(2): 209-214, August 2018